2021
DOI: 10.1371/journal.pone.0253164
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about mother to child transmission of HIV/AIDS, its prevention and associated factors among reproductive-age women in sub-Saharan Africa: Evidence from 33 countries recent Demographic and Health Surveys

Abstract: Background In sub-Saharan Africa (SSA) 90 percent of babies acquired HIV/AIDS from infected mothers. Maternal knowledge about mother to child transmission (MTCT) of HIV/AIDS and its prevention is a cornerstone for elimination of MTCT of HIV/AIDS. Despite this, there is limited evidence about knowledge about MTCT of HIV/AIDS and its prevention and associated factors in SSA. Therefore, this study aimed to assess knowledge of MTCT of HIV/AIDS, its prevention (PMTCT) and, associated factors among reproductive-age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 20 publications
10
26
4
Order By: Relevance
“…The main outcome variable in this study is reproductive women’s comprehensive knowledge on MTCT and EMTCT of HIV in Rwanda. It is a composite score of five [ 5 ] different questions that were similar to those in previous studies [ 2 , 4 , 8 , 10 , 14 ]. The questions included (i) “Now I would like to talk about something else, have you ever heard of HIV/AIDS?”, (ii) “Can HIV be transmitted from mother to her baby during pregnancy?”, (iii) “Can HIV be transmitted from the mother to her baby during delivery?”, (iv) “Can HIV be transmitted from the mother to her baby during breastfeeding?”, (v) “Are there any special drug or medicines that a doctor or a nurse can give to a woman infected with HIV to reduce the risk of transmission to the baby?”.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main outcome variable in this study is reproductive women’s comprehensive knowledge on MTCT and EMTCT of HIV in Rwanda. It is a composite score of five [ 5 ] different questions that were similar to those in previous studies [ 2 , 4 , 8 , 10 , 14 ]. The questions included (i) “Now I would like to talk about something else, have you ever heard of HIV/AIDS?”, (ii) “Can HIV be transmitted from mother to her baby during pregnancy?”, (iii) “Can HIV be transmitted from the mother to her baby during delivery?”, (iv) “Can HIV be transmitted from the mother to her baby during breastfeeding?”, (v) “Are there any special drug or medicines that a doctor or a nurse can give to a woman infected with HIV to reduce the risk of transmission to the baby?”.…”
Section: Methodsmentioning
confidence: 99%
“…The Social Cognitive Theory [ 18 ] and the Information Motivation Behavioral Skills Theory (IMB) [ 19 ] and previous literature [ 1 , 2 , 4 , 8 , 10 , 11 ] provided the theoretical foundation and guided selection of the independent predictors analyzed in this study respectively. The independent predictors have been categorized into Individual level factors such as Respondents age (15–19, 20–24, 25–29, 30–34, 35–39, 40–44, 45–49), Marital status (recoded into Never in union/Not Married, Married/Living with partner, Divorced/Separated/Widowed), Highest educational level (No education, Primary, Secondary, Higher), Religion (Catholics, Protestants, Adventists, Muslim, Traditional & Others), Frequency of reading newspaper/magazine (Not at all, Less than once a week, At least once a week), Frequency of listening to radio (Not at all, Less than once a week, At least once a week), Frequency of watching Television (Not at all, Less than once a week, At least once a week), Wealth Index Combined (Poorest, Poorer, Middle, Richer, Richest), Currently pregnant (No or Unsure, Yes), Visited health facility last 12 months (No, Yes), Covered by Health Insurance (No, Yes), Respondent currently working/Employment status (Employed, Unemployed).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is supported by study in the Sub-Saharan, North and Northeast Ethiopia. 14 16 , 20 Women who live in urban settings have good health-seeking behavior and might have better access to maternal health care services, such as antenatal care (ANC). 21 , 22 The study done in Northeast Ethiopia showed that ANC service utilization has positive significant association with the knowledge of the vertical transmission of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…23 Regardless of the wide availability of PMTCT services, the mother’s knowledge of PMTCT is not satisfactory. 20 , 24 Poor knowledge and practice and negative attitude of pregnant women about MTCT and PMTCT are the main challenges in Ethiopia for the full implementation of PMTCT service. 25 …”
Section: Introductionmentioning
confidence: 99%